Teaching Vocabulary Using Blended Learning Method - Maya Masita (Universitas Cokroaminoto Palopo, 2020)
This is a case study aimed at describing teaching vocabulary based blended learning method. There were 30 students involved in this study. The data were taken using mixed methods by giving an interview and observation. The findings of this study were analyzed using triangulation analysis. The results of this study showed that: 1) vocabulary teaching model based blended learning method create an interactive teaching and learning atmosphere, 2) the students are not familiar with the learning application, so they found difficulties using smartphone in accessing learning application, 3) the internet connection is unstable, so the teacher should prepare another activity, 4) the selection of learning applications that suitable with students need to make the teaching and learning activities more fun, easy to understand, and keep following the development of teaching and learning methods.